Present Tense in Jaffna Tamil and Sinhala - A Contrastive Study: Based on Comrie's Point of View - Senthuran, S. (University of Kelaniya, 2017)
The aim of this research is to find out the similarities and dissimilarities between present tense in Jaffna Tamil and Spoken Sinhala languages. This study is significant as tenses are not similar in all languages. Sinhala has two tenses: past and non-past, whereas Tamil has three: present, past and future. According to Comrie's views, tenses are of two categories namely, absolute tense and relative tense. Tamil and Sinhala languages have the absolute and relative tense categories. Present tense is under the category of absolute tense. Data were collected from written documents and novels. The sample consists of hundred students from University of Jaffna and University of Kelaniya. Collected data were analysed using structural linguistic method, and descriptive and contrastive analysis methods, taking in to consideration Comrie's views on tenses. A number of similarities and dissimilarities between present tense in the two languages are identified. Similarities such as present forms to express future time reference, and both languages having the present tense suffixes and time adverbs to indicate time of an event were highlighted. Further, dissimilarity including the agreement of present tense forms in Tamil with their subject in number, gender and person, unlike in spoken Sinhala were identified..
Keywords: Absolute Tense; Location of Situation; Present Tense; Present Moment; Tamil and Sinhala Languages